The Araguaia fold belt, Brazil: A reactivated Brasiliano-Pan-African cycle (550 Ma) geosuture - Herz, Norman; Hasui, Yociteru [UNESP]; Costa, Joao Batista Sena; Matta, Milton Antonio Da Silva (Elsevier, 1989)
The Araguaia-Tocantins geosuture, which separates the Araguaia Fold Belt (AFB) from the Archean Amazonian Craton, was active in the late Middle Proterozoic. The Baixo Araguaia Supergroup was deposited, consisting of the Estrondo Group (lower quartzites with intercalated schists), Xambioá Formation (schists), and Canto da Vazante Formation (upper feldspathic schists); and the Tocantins Group consisting of the Couto Magalhaës Formation (phyllites, quartzites, slates, limestones, and metacherts) and Pequizeiro Formation (upper chlorite schists); and associated mafic-ultramafic bodies. The deformational history includes four regional phases of deformation within this supracrustal sequence: recumbent folds with vergence to the west; refolding with a N-S trend; an intense crenulation episode; and late thrusting from east to west. Metamorphism is of intermediate or intermediate-high pressure type with garnet, biotite, chlorite, and sericite isograds succeeded by a slightly or non-metamorphosed zone, from east to west. Rocks surrounding sparse gneissic-cored domes contain isograds of staurolite, kyanite, and fibrolite. These isograds are believed to be associated with the 1100 Ma Uruaçuano event. The Brasiliano Orogeny strongly affected the AFB with displacements due to transcurrent reactivation of great and old faults of the basement, slight folding in the supracrustal sequence, intrusion of small granite bodies, and development of domes with associated normal faults. The area underlain by the Estrondo Group was uplifted at this time, causing the deposition of the Rio das Barreiras polymictic conglomerate of the central area. K-Ar and Rb-Sr analyses date this thermo-tectonic event at 550 ± 100 Ma. The Archean basement is exposed in the cores of domes as a granite-gneiss association, the Colméia complex, which shows thermo-tectonic features that may be interpreted as polycyclic imprints (Jequié, Transamazonian?, Uruaçuano, and Brasiliano Events). © 1989.
Keywords: Araguaia Fold Belt; Araguaia-Tocantins geosuture; Brasiliano Orogeny; deformational history; metamorphic history; Proterozoic; Brazil